Facial paralysis with ear droop in calves associated with exposure to steelworks slag, possibly due to vanadium toxicity. Issue 2 (16th March 2022) - Jewell, Natalie; Jones, Jeff; Floyd, Toby; Davies, Gunhild; Payne, Jo
Abstract: A group of 5 to 7‐week‐old calves presented with unusual clinical signs that included facial paralysis and ear droop. Postmortem examination of a single calf ruled out infectious causes and confirmed that the calf had ingested a gritty slag, a by‐product from the steel industry. The slag was being used on a farm on grazing land but had been stored in such a way that the calves had been exposed. Analysis of the ingested material and tissue analysis confirmed the presence of vanadium at concentrations likely to be significant. A literature search confirmed two other similar cases in Sweden and New Zealand where steel slag exposure had been associated with similar clinical signs; in the former case, these had been attributed to acute vanadium toxicity.